2007
DOI: 10.1007/s10620-006-9657-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effects of DA-6034, a New Flavonoid Derivative, in Various Gastric Mucosal Damage Models

Abstract: This study evaluated the gastroprotective activity of DA-6034 against various ulcerogens including ethanol, aspirin, indomethacin, stress, and acetic acid. The basic mechanisms of DA-6034 as a defensive factor such as mucus secretion and endogenous prostaglandin E(2) synthesis were determined. Rats with gastric lesions induced by ethanol-HCl, aspirin, indomethacin, and stress that had been pretreated with DA-6034 orally showed a statistically significant decrease or decreasing tendency of the gastric lesion. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…However, SK-MS10 does not look to be related with PGE 2 in ethanol-induced gastric mucosa damage because a significant increase of PGE 2 was not found in the gastric tissues in spite of activation of COX-2. These results are similar to previous studies [32,33], suggesting a possibility that dominant contributor of PGE 2 level after ethanol administration might be COX-1 instead of COX-2. However, the expression of COX-1 has not been measured in the present study and further experiments are needed.…”
Section: Discussionsupporting
confidence: 92%
“…However, SK-MS10 does not look to be related with PGE 2 in ethanol-induced gastric mucosa damage because a significant increase of PGE 2 was not found in the gastric tissues in spite of activation of COX-2. These results are similar to previous studies [32,33], suggesting a possibility that dominant contributor of PGE 2 level after ethanol administration might be COX-1 instead of COX-2. However, the expression of COX-1 has not been measured in the present study and further experiments are needed.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies about gastroprotective agent such as rebamipide, eupatilin have proposed that prostaglandin-independent mechanisms 3,11,12. Taiwan study showed that sesamol potently reduced diclofenac-induced mucosal damage, but neither increased nor maintained diclofenac-induced decreases of PGE 2 , mucus, or COX activity 35.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are prostaglandin independent mechanisms including neutrophil activation,7 hypermotility,8 oxygen free radicals,9 and mucosal proinflammatory cytokines 10. In part due to increasing concern about gastrodefensive factors, gastroprotective agent such as rebamipide and eupatilin have been developed 3,11,12…”
Section: Introductionmentioning
confidence: 99%
“…This flavonoid reliably decreased damage frequency caused by ethanol, aspirin, indomethacin, or specific stress. 16 A known PG synthesis stimulator in the stomach mucosa is the hormone gastrin, produced by G-cells. 17 In the present study, serum gastrin-17 was measured before and after the therapy in both groups.…”
Section: Discussionmentioning
confidence: 99%